"Janus" Puzzle: a Case of Creative Application of Marxist Theory in the Soviet Lithuanian Historiography? - Švedas, Aurimas (Lietuvos istorijos studijos, 2005)
Academician Juozas Jurginis was one of the most outstanding figures in the Soviet Lithuanian historiography. Analysis of his most fundamental book "The Strengthening of Serfdom in Lithuania" disclosed subtle symptoms of "erosion" in the Soviet version of Marxism. Resting on distinctions suggested by A. Bumblauskas (Communist pragmatism, Stalinism - Leninism, Marxism), the analysis regards this study as an effort to dissociate from the Stalinism-Leninism. Being a virtuosic master of Marxist theory, J. Jurginis noticed and emphasized the problem of different ways in which serfdom and feudalism developed in Eastern and Western Europe. Moreover, the region of Eastern Europe was perceived by him as uneven in terms of social and economic relations. In essence, J. Jurginis formulated "ideologically dangerous" hints indicating that Russia and Lithuania were qualitatively different countries in their historical development. J. Jurginis did not attribute Russia to the "maximum" region of Western Europe, while Lithuania according to his conception was close to this civilization space. These insights lead to the conclusion that J. Jurginis covertly challenged stereotypes of the Soviet historiography.
Keywords: -